2020
DOI: 10.1016/j.redox.2020.101634
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 regulates hepatic macrophage polarization via directly targeting PKM2 and ameliorates NASH

Abstract: Nonalcoholic steatohepatitis (NASH), the progressive form of nonalcoholic fatty liver disease (NAFLD), is becoming a common chronic liver disease with the characteristics of steatosis, inflammation and fibrosis. Macrophage plays an important role in the development of NASH. In this study, Annexin A5 (Anx A5) is identified with the special effect on hepatic macrophage phenotype shift from M1 to M2. And it is further demonstrated that Anx A5 significantly switches metabolic reprogramming from glycolysis to oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 48 publications
2
61
0
1
Order By: Relevance
“…Annexin A5 (Anx A5), a member of the annexin family, switches metabolic reprogramming from glycolysis to oxidative phosphorylation in hepatic macrophages via interacting with pyruvate kinase M2 (PKM2). This metabolic reprogramming process stimulates the polarisation of hepatic macrophages and a phenotypic switch from M1 to M2, thereby ameliorating steatosis, inflammation, and liver fibrosis in the HFD NASH model 118 . These findings indicate a dual role of macrophage metabolism in the pathophysiology of liver fibrosis.…”
Section: Hepatic Macrophages In the Regression Of Liver Fibrosismentioning
confidence: 75%
“…Annexin A5 (Anx A5), a member of the annexin family, switches metabolic reprogramming from glycolysis to oxidative phosphorylation in hepatic macrophages via interacting with pyruvate kinase M2 (PKM2). This metabolic reprogramming process stimulates the polarisation of hepatic macrophages and a phenotypic switch from M1 to M2, thereby ameliorating steatosis, inflammation, and liver fibrosis in the HFD NASH model 118 . These findings indicate a dual role of macrophage metabolism in the pathophysiology of liver fibrosis.…”
Section: Hepatic Macrophages In the Regression Of Liver Fibrosismentioning
confidence: 75%
“…Moreover, administration of AnxA5 fused to stromal-derived factor 1, a cytokine that protects the heart from ischaemic injury, accumulated at the myocardium, probably via binding to PS on apoptotic cells, and provided cardioprotection, as judged by attenuated apoptosis, enhanced angiogenesis, reduced infarcted size and improved cardiac function after MI [ 259 ]. Finally, AnxA5 administration improved steatosis, inflammation and fibrosis in nonalcoholic steatohepatitis [ 260 ]. Interestingly, the underlying mechanism in the latter studies might not involve AnxA5 binding to PS, but AnxA5 interacting with pyruvate kinase 2, leading to metabolic reprogramming from glycolysis to oxidative phosphorylation in macrophages [ 260 ] ( Table 5 d).…”
Section: Anxa5mentioning
confidence: 99%
“…Finally, AnxA5 administration improved steatosis, inflammation and fibrosis in nonalcoholic steatohepatitis [ 260 ]. Interestingly, the underlying mechanism in the latter studies might not involve AnxA5 binding to PS, but AnxA5 interacting with pyruvate kinase 2, leading to metabolic reprogramming from glycolysis to oxidative phosphorylation in macrophages [ 260 ] ( Table 5 d).…”
Section: Anxa5mentioning
confidence: 99%
“…In the present study, it was demonstrated that CeNP-PEG increase mitochondrial OXPHOS activity as judged by mitochondrial OCR and also decrease glycolytic activity as judged by ECAR. [36,37] Since EMT is accompanied by the increased expression of glycolytic enzymes. In our study, it was demonstrated that the protein levels of HK1 and HK2, which are the critical metabolic kinase of the aerobic glycolysis, significantly decreased after treatment with CeNP-PEG.…”
Section: Discussionmentioning
confidence: 99%